Webcams as a Remote Tool for Eco-ethological Research: A Study on the Alpine Chough - Vallino, Cristina; Yoccoz, Nigel Gilles; Rolando, Antonio; Delestrade, Anne (Frontiers in Environmental Science, 2021)
Methods and devices specifically created for remote animal surveys and monitoring are becoming increasingly popular and effective. However, remote devices are also widely used in our societies for different, not scientific, goals. Ski resorts in the European Alps, for instance, use webcams to share panoramic views and promote themselves in the industry of winter recreational activities. We tested preinstalled webcam effectiveness as a remote tool for eco-ethological studies. Our target species was the Alpine Chough Pyrrhocorax graculus, a social and opportunistic corvid species of high mountain environments that attends ski resorts to feed on scraps discarded by high elevation bars and restaurants. We studied the effect of the winter presence of tourists and weather conditions on flocking behaviour at ski resorts. We used flock size and time spent at the ski resort as response variables, and assessed how strongly they were related to the number of tourists and weather conditions. We analysed about 13,500 pictures taken at 10 minute intervals at three ski resorts sites in the European Alps in France, Italy and Switzerland. The number of birds was very different among the three study sites. Flock size and time spent were related to the same environmental drivers, but with different effect sizes in the three areas. The daily maximum flock size and the time spent at ski resorts increased with the number of tourists and decreased with temperature at two sites out of three. We also found that the presence of fresh snow caused a decrease in the maximum flock size in all ski resorts. In conclusion, Alpine Choughs modulated their presence at the ski resorts according to human presence and weather conditions, but these responses were context-dependent. Preinstalled webcams, despite a few caveats, can therefore be successfully employed in eco-ethological research. Webcams around the world are increasing in number and represent therefore a large potential resource. If webcam companies could be engaged to make some slight adjustments, without compromising their goals, then this could offer a new way to collect eco-ethological data.